Ethinyl estradiol and levonorgestrel in a transdermal contraceptive delivery system - Intira Sriprasert (2018)
© 2015 Informa UK, Ltd. Introduction: The new transdermal contraceptive delivery system (TCDS) developed by Agile Therapeutics containing ethinyl estradiol and levonorgestrel (EE/LNG) is a reversible contraceptive method that maintains stable serum levels of both estrogen and progestin, and has efficacy similar to that of combination oral contraceptives (COC).Areas covered: We provided information of this new TCDS compared with the only TCDS available on the market that contains EE and norelgestromin, and has a higher EE exposure than a COC with 35 μg of EE potentially increasing the risk of venous thromboembolism. The article will summarize finding from clinical studies Phase I, II and III of EE/LNG TCDS.Expert opinion: The development of the lower dose EE/LNG TCDS has demonstrated less EE exposure. The serum levels of EE and LNG were stable and comparable between various application sites and daily life conditions. Moreover, the EE/LNG TCDS showed comparable efficacy among obese and non-obese users. However, the Pearl index of this EE/LNG TCDS is questionable and the problem of compliance is a potential confounder of the results. The current Phase III efficacy study will contribute to a further evaluation of compliance and efficacy and will be completed in 2016.